2006
DOI: 10.1196/annals.1369.010
|View full text |Cite
|
Sign up to set email alerts
|

Genes and Gene Expression in the Brains of Human Alcoholics

Abstract: Chronic alcohol misuse by human subjects leads to neuronal loss in regions such as the superior frontal cortex (SFC). Propensity to alcoholism is associated with several genes. gamma-Aminobutyric acid (GABA)(A) receptor expression differs between alcoholics and controls, whereas glutamate receptor differences are muted. We determined whether genotype differentiated the regional presentation of GABA(A) and glutamate-NMDA (N-methyl-d-aspartate) receptors in SFC. Autopsy tissue was obtained from alcoholics withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Thus, Dodd and colleagues reported that the GABRB2 gene, which encodes for the β2 subunit, did not influence the β2 subunit expression; rather, expression of β3 subunit was increased in controls with GABRB2-1,2 genotype, but not in alcoholics with the same genotype (Dodd et al 2004). Furthermore, aldehyde dehydrogenase ADH1C, D2 dopamine receptor DRD2B, excitatory amino acid transporter 2 EAAT2, and apolipoprotein E APOE genotypes modulate GABA A receptor β subunit expression in superior frontal cortex toward a less-effective form of the receptor (Dodd et al 2004, 2006). Alleles associated with alcoholism also appear to reduce the β3:β2 ratios in alcoholic’s superior frontal cortex.…”
Section: Human Alcoholicsmentioning
confidence: 99%
“…Thus, Dodd and colleagues reported that the GABRB2 gene, which encodes for the β2 subunit, did not influence the β2 subunit expression; rather, expression of β3 subunit was increased in controls with GABRB2-1,2 genotype, but not in alcoholics with the same genotype (Dodd et al 2004). Furthermore, aldehyde dehydrogenase ADH1C, D2 dopamine receptor DRD2B, excitatory amino acid transporter 2 EAAT2, and apolipoprotein E APOE genotypes modulate GABA A receptor β subunit expression in superior frontal cortex toward a less-effective form of the receptor (Dodd et al 2004, 2006). Alleles associated with alcoholism also appear to reduce the β3:β2 ratios in alcoholic’s superior frontal cortex.…”
Section: Human Alcoholicsmentioning
confidence: 99%
“…It is well known that this system is modulated by both inhibitory and stimulatory inputs, including GABAergic and glutamatergic neurons (Johnson, 2005). Chronic alcohol usage may be associated with alteration in the subunit composition of the GABA receptors in human (Dodd et al, 2006). The GABA A receptor in particular may be pivotal in the sex disparity in response to alcohol intake.…”
Section: Gaba Receptorsmentioning
confidence: 99%
“…The GABA A receptor in particular may be pivotal in the sex disparity in response to alcohol intake. Alcohol is known to alter GABAergic neurotransmission through GABA A receptor, which plays an essential role in acute response to alcohol, alcohol dependence and self-administration (Grobin et al, 1998; Dodd et al, 2006). Activation of the GABA A receptor also mediates behavioral responses including, motor ability, anxiolytic responses, and sedating responses to alcohol (Grobin et al, 1998; Abramov et al, 2006).…”
Section: Gaba Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms by which alcohol achieves its short-and long-term effects on the brain are largely unknown, although ion channels and neurotransmitter receptors have become the targets of intense inquiry (Worst and Vrana, 2005). A number of excellent studies using gene arrays have identified a variety of genes that are upregulated or downregulated by short-or long-term exposure to alcohol in experimental animals and man (Lewohl et al, 2000;Dodd et al, 2006;Mulligan et al, 2006). Despite these investigations, little is known of the molecular mechanisms by which alcohol might alter transcriptional efficiency (Wilke et al, 1994;Hassan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%